Analisis Pengaruh Jumlah Unit Usaha Industri Mikro dan Kecil (IMK), Tenaga Kerja IMK dan Pendapatan IMK Terhadap Pertumbuhan Ekonomi di Indonesia pada Tahun 2010-2020 - Azzahra, Sarah; Srivani, Musbatiq; Rizky, Bintang; Sufiawan, Nur Ari (Indonesian Research Journal on Education, 2023)
This study aims to determine and analyze whether the number of IMK business units IMK workforceand IMK income has a positive effect on the economic growth of Indonesia in 2010-2020. Thechallenge resource used in this research is secondary data obtained through the official website of the Indonesian Central Statistics Agency with a scope of 2010-2020. This study uses quantitative methods, according to Sandu (2015) quantitative data is data in the form of numbers or numbers. The data used in this study is data on the number of IMK business units, IMK workforce and IMK income in Indonesia and the total GDP of Indonesia at constant prices. The data analysis method used is Multiple Linear Regression. The source of data used in this study is secondary data, secondary data is the power obtained from the agency or publication from parties related to the object of research. The secondary data used is in the form of annual time series data for the period 2010-2020 which is obtained from the publication of BPS Indonesia. The results showed that the variable number of IMK business units had a significant effect on Indonesia's economic growth. Variables IMK labor and IMK income have no significant effect on IMK income on Indonesia's economic growth of 91.76% and 8.24% of economic growth Indonesia is explained by other variables.